Shahid Al-Quran in kitab tashil nayl al-amani by sheikh ahmad al-fatani - Zamri, Rajab; Zulazhan, Ab. Halim; Kamarul Shukri, Mat Teh (2015)
Fatani is a famous region in the south Thailand, which had produced many Islamic scholars in its country. Wan Sheikh Ahmad bin Muhammad Zain Al-Fatani (Sheikh Ahmad) seems known with his writings in variety of disciplines, especially through the book of Arabic grammar Tashil Nayl Al-Amani fi Sharh 'Awamil Al-Jurjani (Tashil). This study aims to highlight the efforts of Sheikh Ahmad which used many shahid al-Quran in his writings and had contributed them to the development of teaching and learning Arabic grammar not only in its country but to the entire Islamic world. This study is a qualitative using documentary analysis. The results showed that Sheikh Ahmad has his own personal characteristics that are pure, follow various disciplines of knowledge, active in the fields of writing, which he controls and able to trace used of shahid al-Quran in a comprehensive manner in order to practice of teaching and learning the Arabic grammar, especially through the kitab Tashil. This study discloses the personality of Sheikh Ahmad and his gold contribution can be recognized as a niche in the whole archipelago dimension Arabic grammar.